The Need to Address Fragmentation and Silos in Mortality Information Systems: The Case of Ghana and Peru - Daniel Cobos Muñoz; Daniel Cobos Muñoz; Carmen Sant Fruchtman; Carmen Sant Fruchtman; Janet Miki; Javier Vargas-Herrera; Javier Vargas-Herrera; Sarah Woode; Fidelia A. A. Dake; Benjamin Clapham; Don De Savigny; Don De Savigny; et al. (Frontiers Media S.A., 2022)
Objectives: We aimed to understand the information architecture and degree of integration of mortality surveillance systems in Ghana and Peru.Methods: We conducted a cross-sectional study using a combination of document review and unstructured interviews to describe and analyse the sub-systems collecting mortality data.Results: We identified 18 and 16 information subsystems with independent databases capturing death events in Peru and Ghana respectively. The mortality information architecture was highly fragmented with a multiplicity of unconnected data silos and with formal and informal data collection systems.Conclusion: Reliable and timely information about who dies where and from what underlying cause is essential to reporting progress on Sustainable Development Goals, ensuring policies are responding to population health dynamics, and understanding the impact of threats and events like the COVID-19 pandemic. Integrating systems hosted in different parts of government remains a challenge for countries and limits the ability of statistics systems to produce accurate and timely information. Our study exposes multiple opportunities to improve the design of mortality surveillance systems by integrating existing subsystems currently operating in silos.